Implementation of learning processes using total quality management at universidade oriental and universidade Dili of Timor Leste - Guterres, Antonio; Goncalves, Agostinho dos Santos; Pereira, Sebastiao (Edelweiss Applied Science and Technology, 2025)
Quality is the most important agenda faced by all educational institutions in improving their quality. The quality dimension can be seen from two points of view: the process of producing each product and the quality produced by each product, including product dimensions (goods) such as function, performance, reliability, strength, ease of care, aesthetics, and suitability, as well as the service dimension (service) consisting of speed of response, resources, friendliness, and accuracy. The objective of this study is to understand how the learning process is insightful for total quality management at the existing universities in Timor Leste. This research includes planning, implementation, evaluation, and follow-up learning, as well as factors affecting the learning process at the universities in Timor Leste. This research is a qualitative study using a case study model. Data were collected through interviews, observations, and documentation. The collected data were then analyzed in depth by examining a single case through coding, data display, and drawing conclusions in each case, followed by cross-case analysis to arrange the concepts and points of the existing cases. Data validity was ensured through credibility, transparency, dependency, and confirmability. The results of this study show that total quality management-oriented learning planning should involve the entire academic community, taking into account the needs and customer satisfaction (students) by using instructional guides, learning tools, and an oriented learning process that includes human resources, facilities, media, and learning resources, as well as the commitment of the academic community, the academic environment and culture, and the motivation and interest of the students.